The Choroid Plexus in Healthy and Diseased Brain - Kaur, Charanjit; Rathnasamy, Gurugirijha; Ling, Eng-Ang (Journal of neuropathology and experimental neurology, 2016)
The choroid plexus is composed of epithelial cells resting on a basal lamina. These cells produce the cerebrospinal fluid (CSF), which has many functions including rendering mechanical support, providing a route for some nutrients, removing by-products of metabolism and synaptic activity, and playing a role in hormonal signaling. The choroid plexus synthesizes many growth factors, including insulin-like, fibroblast, and platelet-derived growth factors. The tight junctions located between the apical parts of the choroid plexus epithelial cells form the blood-CSF barrier (BCSFB), which is crucial for the homeostatic regulation of the brain microenvironment along with the blood-brain barrier (BBB). Morphological changes such as atrophy of the epithelial cells and thickening of the basement membrane suggest altered CSF production occurs in aging and in Alzheimer disease. In brain injuries and infections, leukocytes accumulate in the CSF by passing through the choroid plexus. In inflammatory CNS diseases (eg, multiple sclerosis), pathogenic autoreactive T lymphocytes may migrate through the BBB and BCSFB into the CNS. The development of therapeutic strategies to mitigate disruption of the BCSFB may be helpful to curtail the entry of inflammatory cells into the CSF and hence reduce inflammation, thereby overcoming choroid plexus dysfunction in senescence and in various diseases of the CNS.